Self-representation of children suffering from congenital heart disease and maternal competence - Giovanna Perricone; Concetta Polizzi; Francesco De Luca (MDPI AG, 2013)
Child development may be subject to forms of motor, physical, cognitive and self-representation impairments when complex congenital heart disease (CHD) occurs. In some cases, inadequacy of both self-representation as well as the family system are displayed. It seems to be important to search the likely internal and external resources of the CHD child, and the possible connections among such resources, which may help him/her to manage his/her own risk condition. The research project inquires the possible resources related to the self-representation and self-esteem levels of the CHD child, and those related to maternal self-perception as competent mothers. A group of 25 children (mean age = 10.2; SD=1.8) suffering from specific forms of CHD, and a group made up of their relative mothers (mean age = 38.2; SD=5) were studied. The tools used were the Human Figure Drawing, to investigate child body-related self-representation; the TMA scale (Self-esteem Multidimensional Test), to investigate the child's self-esteem; and the Q-sort questionnaire, to assess how mothers perceived their maternal competence. Data concerning the likely correlations between the child's self-representation and the maternal role competence show [that] positive correlations between some indicators of maternal competence, specific aspects of CHD children's self-representation (mothers' emotional coping and children's self-image adequacy) and self-esteem (mothers' emotional scaffolding and children's self-esteem at an emotional level). By detecting the occurrence of specific correlations among resources of both child and mother, the study provides cardiologists with information that is useful for building a relationship with the families concerned, which would seem to enhance the quality of the process of the cure itself.